Heat-conductive resin material

A cost-effective thermally conductive resin material with high thermal conductivity is achieved by blending silicon carbide and alumina particles in specific ratios, addressing the expense and thermal resistance issues of previous materials.

JP2025007007AInactive Publication Date: 2025-01-17MITSUBISHI MATERIALS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023108117
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing thermally conductive resin materials using silicon carbide as the sole filler are expensive, and those combining silicon carbide with alumina particles suffer from higher thermal resistance and increased costs.

Method used

A thermally conductive resin material comprising a blend of silicon carbide and alumina particles with specific size ranges and ratios, along with a resin matrix, to achieve low cost and high thermal conductivity.

Benefits of technology

The resin material achieves thermal conductivity of 2.0 W/mK or more with an Asker C hardness of 75 or less, enabling efficient heat dissipation in electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007007000001_ABST
    Figure 2025007007000001_ABST
Patent Text Reader

Abstract

To provide a heat-conductive resin material which is low in cost and is excellent in heat conductivity.SOLUTION: A heat-conductive resin material has a resin and a filler dispersed in the resin, wherein the filler has silicon carbide particles having a first average particle diameter and alumina particles, a first average particle diameter of the silicon carbide particles is within a range of 10 μm or more and 100 μm or less, a ratio of the filler contained in the heat-conductive resin material is 65 vol.% or more and 80 vol.% or less, and the heat-conductive resin material has heat conductivity of 3.0 W / mK or more and Asker C hardness of 75 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermally conductive resin material in which a thermally conductive filler is dispersed in a resin. [Background technology]

[0002] In recent years, the amount of heat generated by electrical components is increasing with the advancement of the performance of personal computers and smartphones and the development of electric vehicles and fuel cell vehicles. For example, lithium ion batteries for automobiles generate a lot of heat because they output a large current of power continuously for a long period of time, and it is necessary to efficiently dissipate the large amount of heat generated to the outside. For this reason, thermally conductive resin materials with excellent thermal conductivity are sometimes used as heat dissipation materials for electrical components such as lithium ion batteries and IC chips. In this case, it is desirable for the thermally conductive resin material to be soft, since it is placed between the heat source and a component such as a case with a low temperature.

[0003] Conventionally, thermally conductive resin materials include those in which thermally conductive fillers with excellent thermal conductivity are dispersed in resin materials with excellent moldability. 2 O 3 Known examples of such inorganic materials include silicon carbide (SiC) and inorganic materials such as fluorine (fluorine), etc. For example, Patent Document 1 discloses a thermally conductive sheet using a mixture of two sizes of silicon carbide particles, i.e., silicon carbide particles with an average particle size of 50 μm to 100 μm and silicon carbide particles with an average particle size of 10 μm or less, as a thermally conductive filler.

[0004] Patent Document 2 discloses a thermally conductive material using alumina particles and two types of silicon carbide particles, large and small, as thermally conductive fillers. The large silicon carbide particles have an average particle size of 50 to 100 μm, and the small silicon carbide particles have an average particle size of 5 to 10 μm. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2001-139733 A [Patent Document 2] JP 2003-197833 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, in Patent Document 1, the thermally conductive filler is made only of silicon carbide, which is more expensive than alumina and the like, so a semiconductor device using this as a thermally conductive sheet for heat dissipation has the problem of high manufacturing costs.

[0007] In addition, in Patent Document 2, by mixing low-cost alumina particles in addition to silicon carbide particles of two different particle sizes, the cost of the thermal conductive material can be reduced, but there is an issue that the thermal resistance is higher than when silicon carbide particles are used alone.

[0008] The present invention has been made in consideration of the above-mentioned circumstances, and has an object to provide a thermally conductive resin material that is low-cost and has excellent thermal conductivity. [Means for solving the problem]

[0009] In order to solve the above problems, a thermally conductive resin material according to one embodiment of the present invention proposes the following measures. (1) A thermally conductive resin material according to a first aspect of the present invention is a thermally conductive resin material having a resin and a filler dispersed in the resin, the filler comprising silicon carbide particles and alumina particles, the silicon carbide particles having an average particle size in the range of 10 μm or more and 100 μm or less, the proportion of the filler in the thermally conductive resin material being 65% by volume or more and 80% by volume or less, the thermal conductivity of the thermally conductive resin material being 2.0 W / mK or more, and the Asker C hardness being 75 or less.

[0010] (2) A second aspect of the present invention is characterized in that, in the thermally conductive resin material of the first aspect, the alumina particles are composed of first alumina particles having an average particle diameter of 1.0 μm or more and less than 10 μm, and second alumina particles having an average particle diameter of 0.1 μm or more and less than 1.0 μm.

[0011] (3) A third aspect of the present invention is characterized in that, in the thermally conductive resin material of the second aspect, a compounding ratio (volume %) of the silicon carbide particles to the first alumina particles is in the range of 60:40 to 90:10.

[0012] (4) A fourth aspect of the present invention is characterized in that, in the thermally conductive resin material of the second or third aspect, the compounding ratio (volume %) of the total of the silicon carbide particles and the first alumina particles to the second alumina particles is in the range of 85:15 to 65:35.

[0013] (5) A fifth aspect of the present invention is characterized in that, in the thermally conductive resin material of any one of the second to fourth aspects, the particle shape of the first alumina particles is either plate-like or polyhedral, or both.

[0014] (6) A sixth aspect of the present invention is the thermally conductive resin material according to any one of the first to fifth aspects, characterized in that the resin contains at least one of a silicone resin and a urethane resin.

[0015] (7) A seventh aspect of the present invention is the thermally conductive resin material according to any one of the first to sixth aspects, characterized in that the thermal conductivity of the thermally conductive resin material is 6.0 W / mK or more. Effect of the Invention

[0016] According to the present invention, it is possible to provide a thermally conductive resin material that is low cost and has excellent thermal conductivity. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a schematic diagram showing a thermally conductive resin material according to one embodiment of the present invention. [Diagram 2] 1 is a SEM photograph showing (A) silicon carbide particles, (B) first alumina particles, and (C) second alumina particles used in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, a thermally conductive resin material according to one embodiment of the present invention will be described. The following embodiment is specifically described to better understand the gist of the invention, and does not limit the present invention unless otherwise specified. In addition, the drawings used in the following description may show the main parts enlarged for convenience in order to make the features of the present invention easier to understand, and the dimensional ratios of each component may not necessarily be the same as the actual ones.

[0019] FIG. 1 is a schematic diagram showing a thermally conductive resin material according to one embodiment of the present invention. The thermally conductive resin material 10 of this embodiment has a resin 11 and a filler 12 dispersed in this resin 11 . The resin 11 may be selected depending on the intended use of the thermally conductive resin material, and examples thereof include silicone resin and urethane resin.

[0020] Silicone resins are polymeric compounds having a main skeleton formed by siloxane bonds. Silicone resins include modified silicone resins into which various organic groups have been introduced. Examples of modified silicone resins include polyimide-modified silicone resins, polyester-modified silicone resins, urethane-modified silicone resins, acrylic-modified silicone resins, olefin-modified silicone resins, ether-modified silicone resins, alcohol-modified silicone resins, fluorine-modified silicone resins, amino-modified silicone resins, mercapto-modified silicone resins, and carboxy-modified silicone resins.

[0021] Examples of the urethane resin include polyol-type urethane resin and polyester-type urethane resin.

[0022] The filler 12 is dispersed in the resin as described above to enhance thermal conductivity, and includes silicon carbide particles 21 and alumina particles 22. The silicon carbide particles 21 are made of silicon carbide (SiC) in a granular form, and in this embodiment, silicon carbide for polishing is used. Since the shape is polyhedral, the contact area is larger than that of a sphere, which has the advantage of reducing thermal resistance. The average particle size of the silicon carbide particles 21 is in the range of 10 μm or more and 100 μm or less, and preferably 30 μm or more and 80 μm or less. The average circularity of the silicon carbide particles 21 of this embodiment is about 0.50 to 0.80.

[0023] The alumina particles 22 are aluminum oxide (Al 2 O 3 In this embodiment, alumina having a particle shape of either plate or polyhedron, or both, is used.

[0024] The alumina particles 22 of this embodiment use two types of alumina particles having different average particle diameter ranges. That is, the first alumina particles (large particle diameter alumina particles) 22A having an average particle diameter of 1.0 μm or more and less than 10 μm, and the second alumina particles (small particle diameter alumina particles) 22B having an average particle diameter of 0.1 μm or more and less than 1.0 μm are used. That is, the alumina particles 22 of this embodiment have a particle size distribution with two peaks (bimodal).

[0025] The average particle diameters of the first alumina particles 22A and the second alumina particles 22B are peak values ​​among values ​​measured using a laser diffraction scattering type particle size distribution measuring device (MT3300EXII: manufactured by Microtrack Bell Co., Ltd.). The average circularity of the first alumina particles 22A of this embodiment is about 0.50 to 0.80. The average circularity of the filler was measured by analyzing powder photographed at 500 times with a SEM (SU8230: manufactured by Hitachi High-Technologies Corporation) using image analysis software Fiji (Fiji: ImageJ, with 'Batteries Included').

[0026] The compounding ratio of the particles constituting the filler is preferably such that the compounding ratio (volume %) of silicon carbide particles 21 to first alumina particles 22A is in the range of 60:40 to 90:10. Also, the compounding ratio (volume %) of the total of silicon carbide particles 21 and first alumina particles 22A to second alumina particles 22B is preferably in the range of 85:15 to 65:35. It is sufficient that either one or both of these compounding ratios are satisfied.

[0027] In the thermally conductive resin material 10 of the present embodiment, as described above, the average particle diameters of the silicon carbide particles 21, the first alumina particles 22A, and the second alumina particles 22B constituting the filler 12 are set to be in different ranges (trimodal), so that the first alumina particles 22A and the second alumina particles 22B can enter between the silicon carbide particles 21, and the second alumina particles 22B can enter between the first alumina particles 22A. This makes it possible to increase the amount of filler 12 added to the resin 11, thereby improving the thermal conductivity compared to the case where a filler of one type of average particle diameter is used.

[0028] The thermally conductive resin material 10 of the present embodiment preferably further contains a silane coupling agent. The silane coupling agent can be selected from aminosilanes, mercaptosilanes, vinylsilanes, epoxysilanes, methacrylsilanes, and the like, depending on the type of resin 11. By containing such a silane coupling agent, the hardness of the thermally conductive resin material 10 can be adjusted.

[0029] The thermally conductive resin material 10 of the present embodiment having the above-mentioned configuration has a thermal conductivity of 2.0 W / mK or more, preferably 6.0 W / mK or more. Although it is preferable that the thermal conductivity of the thermally conductive resin material 10 is as high as possible, it is generally about 20 W / mK or less.

[0030] Furthermore, the thermally conductive resin material 10 of this embodiment has an Asker C hardness based on JIS K 7312, measured by an Asker C hardness tester, of not more than 75. The Asker C hardness of not more than 75 improves the shape conformability of the thermally conductive resin material 10 of this embodiment, and the thermally conductive resin material 10 can be provided in close contact with an object to which the thermally conductive resin material 10 is to be applied, even if the object to which the thermally conductive resin material 10 is applied has a curved or uneven surface shape.

[0031] According to the thermally conductive resin material 10 of this embodiment, silicon carbide particles 21 and alumina particles 22 having an average particle size in the range of 10 μm or more and 100 μm or less are used as the filler 12 dispersed in the resin 11, and by containing this filler 12 in an amount of 65 volume % or more and 80 volume % or less with respect to the thermally conductive resin material 10, it is possible to obtain a thermally conductive resin material 10 having a thermal conductivity of 2.0 W / mK or more and an Asker C hardness of 75 or less.

[0032] Such thermally conductive resin material 10 has a high thermal conductivity of 2.0 W / mK or more, and therefore when applied to, for example, an IC chip or a lithium ion battery, the generated heat can be rapidly conducted toward a heat dissipation member or the like.

[0033] In addition, the thermally conductive resin material 10 of this embodiment is capable of achieving both excellent thermal conductivity and low cost by using low-cost alumina particles 22 as the filler 12 together with silicon carbide particles 21, which have excellent thermal conductivity but are expensive.

[0034] Although the embodiments of the present invention have been described above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope of the invention and its equivalents as described in the claims, as well as in the scope and spirit of the invention. EXAMPLES

[0035] The effect of the present invention was verified. The resin used to disperse the filler was liquid silicone (model number KE-1051J, manufactured by Shin-Etsu Chemical Co., Ltd.). KE-1051J was prepared by mixing KE-1051J A:KE-1051J B at a ratio of 1:1 (mass ratio). The following fillers were used: (A) Silicon carbide particles 21: Shinano Random GP500 (average particle size 30.7 μm): manufactured by Shinano Electric Smelting Co., Ltd. (B) First alumina particles 22A: ALM-43 (average particle diameter 3.9 μm): manufactured by Sumitomo Chemical Co., Ltd., average circularity 0.65 (C) Second alumina particles 22B: AES-11C (average particle size 0.49 μm): manufactured by Sumitomo Chemical Co., Ltd. Average circularity 0.65 SEM photographs of each particle are shown in FIG.

[0036] The resin described above was mixed with silicon carbide particles (A), first alumina particles (B), and second alumina particles (C) in the ratios shown in Table 1 below using a planetary centrifugal mixer at 2000 rpm, and the rubber mixture to which the mixed powder was added was left to stand at room temperature (25°C) for 24 hours to obtain thermally conductive resin materials (samples) for each experimental example. Then, the Asker C hardness and thermal conductivity of each sample were measured. The Asker C hardness was measured using an Asker rubber hardness tester Type C (manufactured by Kobunshi Keiki Co., Ltd.). The thermal conductivity was measured by a steady-state method using a thermal conductivity measuring device (IE-1237, manufactured by Iwasaki Electric Co., Ltd.). Table 1 shows the particle composition of each experimental example, as well as the measurement results of Asker C hardness and thermal conductivity.

[0037] [Table 1]

[0038] According to the results shown in Table 1, it was confirmed that when the filler content is 78.2 volume %, if the compounding ratio of silicon carbide particles to first alumina particles is in the range of 60:40 to 90:10 (volume %) and the compounding ratio of second alumina particles to the total of silicon carbide particles and first alumina particles is in the range of 15 to 35 volume %, a thermally conductive resin material can be obtained that has high shape conformability due to its low Asker C hardness and has excellent thermal conductivity such as a thermal conductivity of 6.0 W / mK or more. Moreover, as shown in Experimental Example 8, it was confirmed that even when the filler content was as low as 70.0 volume %, a thermally conductive resin material having excellent thermal conductivity of 3.74 W / mK could be obtained. [Industrial Applicability]

[0039] INDUSTRIAL APPLICABILITY The thermally conductive resin material of the present invention, when applied to IC chips, lithium ion batteries, etc., can rapidly conduct the large amount of generated heat toward heat dissipation members, etc. Therefore, it has industrial applicability. [Explanation of symbols]

[0040] 10...Thermal conductive resin material 11...Resin 12…Filler 21...Silicon carbide particles 22...Alumina particles 22A…First alumina particle 22B…Second alumina particles

Claims

1. A thermally conductive resin material having a resin and a filler dispersed in the resin, The filler includes silicon carbide particles and alumina particles, The average particle size of the silicon carbide particles is in the range of 10 μm or more and 100 μm or less, The ratio of the filler contained in the thermally conductive resin material is 65% by volume or more and 80% by volume or less, A thermally conductive resin material, characterized in that the thermal conductivity of the thermally conductive resin material is 2.0 W / mK or more and an Asker C hardness of the thermally conductive resin material is 75 or less.

2. The thermally conductive resin material according to claim 1, characterized in that the alumina particles are composed of first alumina particles having an average particle diameter of 1.0 μm or more and less than 10 μm, and second alumina particles having an average particle diameter of 0.1 μm or more and less than 1.0 μm.

3. 3. The thermally conductive resin material according to claim 2, wherein a compounding ratio (volume %) of the silicon carbide particles to the first alumina particles is in the range of 60:40 to 90:

10.

4. The thermally conductive resin material according to claim 2, characterized in that a compounding ratio (volume percent) of the total of the silicon carbide particles and the first alumina particles to the second alumina particles is in the range of 85:15 to 65:

35.

5. 3. The thermally conductive resin material according to claim 2, wherein the particle shape of the first alumina particles is either a plate shape or a polyhedral shape, or both.

6. 3. The thermally conductive resin material according to claim 1, wherein the resin contains at least one of a silicone resin and a urethane resin.

7. 3. The thermally conductive resin material according to claim 1, wherein the thermal conductivity of the thermally conductive resin material is 6.0 W / mK or more.

Citation Information

Patent Citations

  • Heat conducting sheet and its production

    JP2001139733A

  • Thermal conduction material

    JP2003197833A